Further exploring the "sting of the scorpion": Hydride migration and subsequent rearrangement of norbornadiene to nortricyclyl on rhodium(i) - Tsoureas, Nikolaos; Bevis, Thomas; Butts, Craig P.; Hamilton, Alex; Owen, Gareth R. (Organometallics, 2009)
A new boron-based flexible scorpionate ligand based upon 7-azaindole, Li[Ph(H)B(azaindolyl)2] (Li[phBai]), has been prepared. This ligand, together with the previously reported ligand K[HB(azaindolyl) 3] (K[Tai]), have been used to prepare a range of monovalent group 9 transition-metal complexes. The complexes [M(COD){K3N,N,H-Ph(H) B(azaindolyl)2}] (where M = rhodium, iridium and COD = 1,5-cyclooctadiene) and [Rh(NBD){K3N,N,H-HB(R)(azaindolyl) 2}] (where NBD = 2,5-norbornadiene and R = Ph, azaindolyl) have been prepared. Structural characterization of [M(COD){K3NNH-Ph(H) B(azaindolyl)2}] (where M = rhodium, iridium) and [Rh(NBD){k 3N, N, H-HB(azaindolyl)3}] reveal strong interactions of the B-H functional group with the metal centers, particularly in the case of [Ir(COD){K3N,N,H-Ph(H)B(azaindolyl)2}]. The complex [Rh(NBD){K3N,N,H-HB(azaindolyl)3}] undergoes a further reaction, resulting from hydride migration from boron to the norbornadiene group. Subsequent rearrangement results in the formation of the rhodium-nortricyclyl complex [Rh(nortricyclyl){k4 N,N,-B,N-B(azaindolyl)3}], providing the first nitrogen-based metallaboratrane complex to contain the tetradentate (K4N,N,B,N) coordination mode. © 2009 American Chemical Society.